AYURVEDIC MANAGEMENT OF UNEXPLAINED INFERTILITY- A CASE STUDY (International Journal of Ayurveda and Pharma Research, 2019)
Infertility is a condition in which successful pregnancy has not occurred, despite normal intercourse over 12 months. The cause of female infertility is multifactorial. Ayurveda assures normal pregnancy by proper maintenance of Garbha Samgraha samagris and normalcy of mind. All the causes of female infertility come under the imbalance of Garbha Samgraha Samagri and mind factors. In this case report patient suffered from primary infertility since six years, after allopathic consultation came for ayurvedic treatment. From detailed history involvement of vitiated Vatha, Agnimandhya and stressful mind was noticed. She was treated with Chiruvilwadi kashayam, Dhanwantharam gulika, Jeerakarishtam, Kumaryasavam and Manasamithravatakam for one month.  Took follicular study on next cycle and revealed post ovulatory status on 16th day of cycle. Advised Phalasarpis, Dhanwantharam Gulika and Manasamithravatakam for two weeks. Patient came with positive urine pregnancy test after one week of missed period. The line of treatment followed in this case was to maintain Agni, normalize Vatha and assure proper health to mind. During the second half of the cycle Garbhasthapana medicines were administered. Patient took Dhanwantharam gulika and phalasarpis throughout the first trimester along with regular ante natal check up. Continued Dhanwantharam gulika up to 36 weeks and started Sukhaprasavagritham upto delivery from 36 weeks onwards. She delivered a female baby on 06.05.2018.